2006
DOI: 10.1680/macr.2006.58.5.313
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of concrete containing recycled asphalt pavements

Abstract: Recycled asphalt pavement (RAP) is the removed and/or reprocessed pavement material containing asphalt and aggregate. The use of RAP in asphalt pavement has become common practice in the construction of new, and reconstruction of old, hot-mix asphalt (HMA) pavements. However, little research has been done to examine the potential of incorporating RAP into Portland cement concrete (PCC) to replace virgin aggregate. In a previous study by the first two of the current authors, laboratory-prepared RAP was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(60 citation statements)
references
References 12 publications
2
55
0
3
Order By: Relevance
“…Recent research studies examined the feasibility of incorporating RAP in Portland cement concrete (Huang et al 2005(Huang et al , 2006. Two gradations of RAP (coarse and fine) materials were considered to replace the fresh aggregate from a control concrete mixture.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research studies examined the feasibility of incorporating RAP in Portland cement concrete (Huang et al 2005(Huang et al , 2006. Two gradations of RAP (coarse and fine) materials were considered to replace the fresh aggregate from a control concrete mixture.…”
Section: Introductionmentioning
confidence: 99%
“…While the slump of concrete made with both coarse and fine RAP was higher than that of control mix. The reason could be probably attributed to the asphalt coating around both coarse and fine RAP so that less water could be absorbed by the aggregates (Huang et al 2005(Huang et al , 2006. The strength of concrete made with both coarse and fine RAP decreased the most among the RAP mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies pertaining to the effects of incorporating RAP on the strength developments reveal regularly that the strength decreases as the replacing proportion of virgin aggregates by RAP increases [8][9][10][11][12][13][14][15][16]22,28,29]. To improve the strength of RAP concrete mix, Singh et al [30] found a viable solution by eliminating the contaminants layers (e.g., airborne dusts attached to surface of RAP) of RAP aggregate.…”
Section: Preparation Of Rapmentioning
confidence: 99%
“…However, the replacement ratio of recycled aggregates in concrete is limited to a certain value [5]. Huang et al [6], [7], investigated the effects of using RAP in cement concrete by replacing the coarse and fraction of aggregate with the reclaimed asphalt, and found that the mixtures containing recycled aggregate have a lower tensile and compressive strength than the mixture containing virgin aggregates. However, the mixtures containing recycled asphalt concrete showed to have a higher toughness.…”
Section: Introductionmentioning
confidence: 99%